Gravitational baryogenesis and dark matter from light black holes. Issue 3 (1st March 2022) - Smyth, Nolan; Santos-Olmsted, Lillian; Profumo, Stefano
Abstract: We study a scenario in which the baryon asymmetry is created through Hawking radiation from primordial black holes via a dynamically-generated chemical potential. This mechanism can also be used to generate the observed dark matter abundance, regardless of whether or not the black holes fully evaporate. In the case that evaporation ceases, the observed dark matter abundance is generically comprised of both relic black holes and an asymmetric dark matter component. We show that this two-component dark matter scenario can simultaneously account for the observed baryon asymmetry and the cosmological dark matter, a possibility which evades constraints on either individual candidate.